Optimalisasi Program Penanaman Bibit Kelapa Genjah Entok Sebagai Upaya Pengembangan Pertanian Berkelanjutan - Herdiatmaja, Mustofa; Sari, Aulia Puspita; Sabilah, Ariesta; Lutfiana, Siti; Fadlurrohman, Hafizh Dwipa; Aziza, Fadila Nur; Rizal, Ahmad Ibnu; Maysandri, Imellia; Gunawan, M. Wahyu; Imam, Muhammad Nurcholis; Febriani, Erma (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Sejati Dukuh Hamlet, Sumberarum Village, Moyudan District, Sleman Regency, has good agricultural potential, but faces serious obstacles related to water shortages and less than optimal land management. Around 70% of its population works as farmers, making the agricultural sector the main pillar of the economy. The purpose of this community service is to improve the knowledge by the utilization of village land through planting Entog Dwarf Coconut and planning the construction of reservoirs to overcome the problem of water for agriculture. The methods used include a participatory approach, starting with identifying problems through observation and interviews, followed by program planning that involves the community in socialization and training of cultivation techniques. The results of the activity showed that farmers gained a better understanding of Entog Dwarf Coconut planting techniques, which are effective in dry land. In addition, the initiative to build reservoirs is expected to increase water availability during the dry season. With this program, it is hoped that farmers and the Sejati Dukuh community can develop and thus be able to improve the welfare of the local community